A science-based sector in the making: the formation of the biotechnology sector in two regions. Issue 10 (3rd October 2017) - Angelakis, Antonios; Galanakis, Kostas
ABSTRACT: A science-based sector in the making: the formation of the biotechnology sector in two regions. Regional Studies . This paper analyses two case studies, Skåne-Blekinge in Sweden and the Southern–Eastern region in Ireland, to examine different current development paths for the biotechnology sector. The aim is to codify the process, identifying actions and priorities towards these paths. National innovation systems theory provides the theoretical framework that guided a series of interviews in the two regions. The findings demonstrate that the sustainable development of a science-based sector does not depend on the original priorities or directions, but rather on the level of consistency of those policies and their continuous evolution towards a complete systemic value generation system.